Effects of Stock Trading Volume, Leverage, and Dividend Payout Ratio on Stock Price Volatility - Alvin Maximillian Kartawijaya; Henny Triyana Hasibuan (Syntax Corporation Indonesia, 2024)
This study aims to analyze the impact of stock trading volume, leverage, and dividend payout ratio (DPR) on stock price volatility among companies included in the Kompas100 Index and listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. The data used in this research were obtained from the financial statements available on the official IDX website and additional data from Yahoo Finance. A purposive sampling method was used to select the research sample based on specific criteria. The results of the study indicate that stock trading volume and leverage have a significant positive impact on stock price volatility, while DPR also influences volatility by showing changes that can elicit sharp market reactions. These findings provide important insights for investors and company management regarding factors that can increase risk and uncertainty in stock prices in the market.